Enhancement of the therapeutic efficacy of mesenchymal stem cell-derived exosomes in osteoarthritis - Zehao Zhang; Sheng Zhao; Zhaofeng Sun; Chuanxing Zhai; Jiang Xia; Caining Wen; Yuge Zhang; Yuanmin Zhang (Cellular & Molecular Biology Letters, 2023)
Abstract Osteoarthritis (OA), a common joint disorder with articular cartilage degradation as the main pathological change, is the major source of pain and disability worldwide. Despite current treatments, the overall treatment outcome is unsatisfactory. Thus, patients with severe OA often require joint replacement surgery. In recent years, mesenchymal stem cells (MSCs) have emerged as a promising therapeutic option for preclinical and clinical palliation of OA. MSC-derived exosomes (MSC-Exos) carrying bioactive molecules of the parental cells, including non-coding RNAs (ncRNAs) and proteins, have demonstrated a significant impact on the modulation of various physiological behaviors of cells in the joint cavity, making them promising candidates for cell-free therapy for OA. This review provides a comprehensive overview of the biosynthesis and composition of MSC-Exos and their mechanisms of action in OA. We also discussed the potential of MSC-Exos as a therapeutic tool for modulating intercellular communication in OA. Additionally, we explored bioengineering approaches to enhance MSC-Exos’ therapeutic potential, which may help to overcome challenges and achieve clinically meaningful OA therapies.